2016
DOI: 10.1093/jac/dkw038
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole in conjunction with penicillin neither prevents recurrence nor enhances recovery from peritonsillar abscess when compared with penicillin alone: a prospective, double-blind, randomized, placebo-controlled trial

Abstract: For healthy adult PTA patients treated with incision and drainage, metronidazole neither prevents recurrence nor enhances recovery when combined with penicillin compared with penicillin alone, but instead leads to increased adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…However, antibiotics have side effects, e.g., 1-2% of individuals have allergy to penicillins [42], metronidazole was discussed having ototoxicity [43] and combined with penicillin it may cause nausea and diarrhea [44]. Moreover, the global problem of development of resistance associated with the consumption of antibiotics [45] demands a well indicated and very restricted use of these drugs [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, antibiotics have side effects, e.g., 1-2% of individuals have allergy to penicillins [42], metronidazole was discussed having ototoxicity [43] and combined with penicillin it may cause nausea and diarrhea [44]. Moreover, the global problem of development of resistance associated with the consumption of antibiotics [45] demands a well indicated and very restricted use of these drugs [46].…”
Section: Discussionmentioning
confidence: 99%
“…As part of a previously published double‐blind randomised study with the identifier NCT01255670, the patients were then randomised to receive either penicillin and placebo or penicillin and metronidazole. Independent of the treatment, an equal amount of patients in both treatment groups experienced symptom renewal, nine in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria identified range from group A streptococcus, anaerobic organisms, to several β‐lactamase–producing species . The studies we cite examined antibiotics as independent variables in the treatment of PTA, and all found that patients treated with drainage and penicillin alone had comparable outcomes to those treated with drainage and broad‐spectrum or multiple antibiotic regimens . The route of administration of penicillin appears to be based on patient compliance or inpatient routines, rather than evidence supporting IV versus oral effect on outcome.…”
Section: Best Practicementioning
confidence: 98%
“…1 The studies we cite examined antibiotics as independent variables in the treatment of PTA, and all found that patients treated with drainage and penicillin alone had comparable outcomes to those treated with drainage and broad-spectrum or multiple antibiotic regimens. [2][3][4][5] The route of administration of penicillin appears to be based on patient compliance or inpatient routines, rather than evidence supporting IV versus oral effect on outcome. It should also be noted that the earlier studies 2-4 may not have been sufficiently powered to find increases in treatment failures, if there were any.…”
Section: Best Practicementioning
confidence: 99%
See 1 more Smart Citation